Comparing Elevational Patterns of Taxonomic, Phylogenetic, and Functional Diversity of Woody Plants Reveal the Asymmetry of Community Assembly Mechanisms on a Mountain in the Hengduan Mountains Region - Zhao, Fu; Yang, Tao; Luo, Caifang; Rao, Wenge; Yang, Gengchen; Li, Guo; Shen, Zehao (Frontiers in Ecology and Evolution, 2022)
The contributions and interaction of biotic and abiotic processes in community assembly are crucial for understanding the elevational patterns of biodiversity. The combined analyses of taxonomic, phylogenetic, and functional diversity are necessary to resolve this issue. By investigating vegetation in 24 transects sampled on Hongla Snow Mountain, in the central Hengduan Mountain Ranges in Southwest China, we delineated the elevational vegetation spectrum on the eastern and western slopes, analyzed the elevational variation in taxonomic, phylogenetic, and functional diversity of woody plant species, and compared the community structure of phylogeny and function in the low-elevational shrublands, mid-elevational forests, and alpine shrubs and meadows. The species richness, phylogenetic diversity, and functional diversity of woody plants showed nonstandard hump-shaped patterns with two peaks along the elevational gradient. The community structure of phylogeny and function (including tree height, leaf area, specific leaf area, leaf thickness, bark thickness, and wood density) clustered in the low-elevation shrub communities, being random and over-dispersed in mid-elevational forests. The phylogenic structure was over-dispersed in alpine communities, whereas the functional structure was clustered. Elevational patterns in taxonomic, phylogenetic, and functional diversity, together with the mean and variation in woody plant functional traits, suggested drought stress and freeze stress as environmental filters dominating the assembly of low and high elevation non-forest communities, and a conspicuous effect of biotic facilitation was also suggested for alpine habitats. By contrast, interspecific competition dominated the community assembly of forests at mid-elevations. The difference in biodiversity indices between the west and east slopes reflected the effects of the Indian Monsoon on the geomorphic patterns of ecosystem structure. These results increased our understanding of biodiversity patterns and underlying mechanisms in the Hengduan Mountains of Southwest China and highlighted the priorities for biodiversity conservation in this region.